Psychiatry, racism and crime: the case of Christopher Clunis reconsidered - Cummins, Ian (Frontiers in Psychiatry, 2024)
In December 2022, the death of Christopher Clunis was made public. He had actually died in February 2021. Christopher Clunis was convicted of the manslaughter of a stranger, Jonathan Zito. He attacked Mr Zito at a train station. This paper will argue that this terrible event became a totemic symbol of the wider failings of the policy of community care. The image of Clunis being driven away from Court was repeatedly used in newspaper and other media reports as a reference point. The image reflects a number of long-standing traits in the representation of the “mentally ill.” These are combined with a racial stereotype of Black men. The paper examines historical representations of the mentally ill as a context for a discussion of the Clunis case. The paper uses the work of Stuart Hall as an analytical tool to examine the questions of race and representation, and the moral panic following failings of community care